2012
DOI: 10.1111/j.1749-771x.2012.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Using a video assisted teaching program to reduce the severity of urinary incontinence symptoms in women

Abstract: Urinary incontinence (UI) is still a common chronic health problem affecting physical, psychological and social well-being of women in developing countries. UI is a challenge to women's health because of the number affected and lack of access to affordable care that can cure or relieve associated symptoms especially in resource limited settings. This study explored the prevalence of UI and assessed effectiveness of a Video Assisted Teaching Program for Kegel's Exercises (VATPKE) in reducing severity of UI symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…We found that patients reporting the severity of pelvic floor symptoms included in the study had urinary incontinence, most of whom suffered from stress urinary incontinence. Our results confirmed the effectiveness of eHealth interventions in reducing the severity of urinary incontinence symptoms, which is consistent with earlier studies [ 65 , 66 ]. The importance of eHealth interventions has been demonstrated [ 63 ], and patients can improve their cognition of the disease in real time by using apps and other similar eHealth technologies [ 67 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that patients reporting the severity of pelvic floor symptoms included in the study had urinary incontinence, most of whom suffered from stress urinary incontinence. Our results confirmed the effectiveness of eHealth interventions in reducing the severity of urinary incontinence symptoms, which is consistent with earlier studies [ 65 , 66 ]. The importance of eHealth interventions has been demonstrated [ 63 ], and patients can improve their cognition of the disease in real time by using apps and other similar eHealth technologies [ 67 ].…”
Section: Discussionsupporting
confidence: 93%
“…Compared with traditional care, eHealth interventions showed significant positive effects on several outcome indicators, including quality of life, pelvic floor muscle strength, sexual function, satisfaction, and self-efficacy of women with or at risk of pelvic floor disorders. Women with or at risk of pelvic floor disease may worry about a series of adverse consequences linked to PFD, including a restricted ability to perform activities, skin rashes, and pruritus in the genital area [ 66 ]. A previous survey showed that most individuals would like to gain more knowledge about their pelvic floor status by using the internet, social networking sites, and other online resources [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study showed that the computed 't' value (16.28) is highly significant at 0.05 level of significance, hence the video-assisted teaching was effective in increasing the knowledge of staff nurses regarding the selected obstetrical emergencies during labor. The present study findings are in conformity with the study done by Seshan et al 5 in which they assessed the effectiveness of a video-assisted teaching program to reduce the severity of urinary incontinence symptoms in women. This study explored the prevalence of UI and assessed effectiveness of a video-assisted teaching program for Kegel's exercises (VATPKE) in reducing severity of UI symptoms among community-dwelling women.…”
Section: Discussionsupporting
confidence: 93%
“…The VATPKE used in this study was effective in reducing the severity of selfreported UI symptoms in community-dwelling Indian women. 5 Ramaiah and Siah 6 conducted a study to assess the effectiveness of a video-assisted teaching program regarding management of selected obstetric emergencies among nursing students in selected colleges in Tamil Nadu. The objectives were to assess the level of pre-test and posttest knowledge among nursing students of third-year B.Sc.…”
Section: Discussionmentioning
confidence: 99%